Financial Performance Evaluation Using the EVA Method Approach at PT. Indosat Tbk. (2020-2025 Period) - Dinda Tiara Putri; Raysia Nurazizah Prihastiwi; Chindo Miftahulrizky; Intan Kusumawati; Rendi Irawan Saputra; Vidya Klara Desvina; Yossinomita Yossinomita (Jurnal Administrasi Terapan, 2026)
This study aims to evaluate the financial performance of PT Indosat Tbk using the Economic Value Added (EVA) approach during 2020-2025. The research applies a quantitative descriptive method based on documentation of the company's financial statements. The analysis includes Net Operating Profit After Tax (NOPAT), Invested Capital (IC), Weighted Average Cost of Capital (WACC), Capital Charges (CC), and EVA. The results show that PT Indosat Tbk generated positive EVA in every year observed. EVA amounted to IDR 876.76 billion in 2020, increased to IDR 4,201.99 billion in 2021, decreased to IDR 2,589,26 billion in 2022, IDR 2,366.85 billion in 2023, and IDR 2,091.86 billion in 2024, before rising again to IDR 2,658.38 billion in 2025. These findings indicate that the company's net operating profit after tax exceeded its capital charges, thereby creating economic value for shareholders despite the higher invested capital following the merger. Keywords: EVA; WACC; Financial Performance; Capital Charges; PT Indosat Tbk.